Answer:
The recursive formula for the sequence is;
![a_n=a_(n-1)+4](https://img.qammunity.org/2023/formulas/mathematics/high-school/hbj5x2km5p46xrcl22iio4kppoxrv01l7m.png)
Step-by-step explanation:
The recursive formula is of the form;
![a_n=a_(n-1)+d](https://img.qammunity.org/2023/formulas/mathematics/college/amblrzzydktrclf12rsmm7k1m3myhwksid.png)
Where;
d = common difference.
To determine the common difference, Let us find the difference between two consecutive terms;
![\begin{gathered} d=a_2-a_1 \\ d=-3-(-7) \\ d=-3+7 \\ d=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/t9tpuo12pejpel7pc0mrpyr2rtth5mlxyq.png)
Substituting the common difference.
The recursive formula for the sequence is;
![a_n=a_(n-1)+4](https://img.qammunity.org/2023/formulas/mathematics/high-school/hbj5x2km5p46xrcl22iio4kppoxrv01l7m.png)